Terminological and historical backgrounds of the criminal law development: from the private law sector to the public law sector - Anna Schneiderová; Róbert Jáger (Journal of Modern Science, 2018)
Objectives Description of terminological and historical backgrounds of the criminal law development: from the private law sector to the public law sector